Improvement of the storage stability of cashew nut butter spread using food additives - Atotubo, Karol Mae Ikalina
The effect of BHT (97 ppm), tocopherol (145.5 ppm), potassium sorbate (0.145 percent by weight), the combination of BHT and postassium sorbate and the combination of tocopherol and potassium sorbate on the general acceptability of cashew nut butter spread were compared.